A225 INFERIOR VENA CAVA STENOSIS AFTER HEPATIC LOBECTOMY: A RARE CAUSE OF PORTAL HYPERTENSION AND REFRACTORY ASCITES. (4th March 2021) - Collins, A W; Brahmania, M; Tsoi, K
Abstract: Background: Inferior vena cava (IVC) stenosis is a rare occurrence in post-liver transplant patients, affecting less than 3% of recipients. IVC stenosis is rarely described in non-transplant patients or considered in the differential of portal hypertension and refractory ascites. Patients with IVC stenosis may experience lower extremity edema, dyspnea, ascites and other signs of portal hypertension. Aims: We describe a case of portal hypertension and refractory ascites secondary to IVC stenosis following hepatic lobectomy. Methods: Case report. Results: We report a 61-year-old woman with a history of diabetes, obesity status post sleeve gastrectomy and solitary neuroendocrine tumor of the right hepatic lobe, adjacent to the porta hepatis with no evidence of metastasis. She underwent a laparoscopic right hepatectomy with wedge resection (<5 cm) in segment 4 to remove the neuroendocrine tumor in 2016. Surgery also included an intraoperative cholangiogram and placement of intra-ductal stent using endoscopic retrograde cholangiopancreatography (ERCP) technology as well as significant adhesiolysis along the IVC, right hepatic vein and biliary tract. In February 2020, the patient was referred to Hepatology for evaluation of new ascites. Imaging did not demonstrate evidence of tumor recurrence or features of cirrhosis but identified a new findings of portal hypertension and moderate ascites. Common causes of chronic liver disease were excluded and hepatic synthetic function was normal. Paracentesis revealed a high serum albumin ascites gradient (SAAG; 20 g/L) and a high ascitic fluid protein (34 g/L). Although these findings were suggestive of cardiac ascites, a 2D echocardiogram was normal. A trans-jugular liver biopsy was attempted in July 2020. The right atrial pressure was 8 mmHg and inferior vena cava (IVC) pressure was 22 mmHg at the level of the liver. Loss of pulsation suggested hemodynamically significant stenosis of the hepatic IVC. The wedged hepatic venous pressure was 3 mmHg and the calculated portal systemic gradient was 4 mmHg. A trans jugular biopsy failed due to unfavourable anatomy. These findings, taken in conjunction with previous results, suggested non-cirrhotic post-hepatic portal hypertension. Subsequent computed tomography imaging confirmed stenosis of the hepatic portion of the IVC and this was felt to be the ultimate cause of the portal hypertension. She has since been referred back to interventional radiology (IR) for consideration of balloon angioplasty dilation of the IVC stenosis as well as additional testing to determine if there is any underlying hepatic fibrosis related to congestive hepatopathy. Conclusions: IVC stenosis post hepatic lobectomy is a rare phenomenon described in the literature but warrants high suspicion in cases of refractory ascites. Funding Agencies: None